In Vitro Evaluation of the Antimicrobial and Antimycobacterial Activities of Solanum guaraniticum A. St.-Hil. Leaves - Marina Zadra,Mariana Piana,Aline Augusti Boligon,Thiele Faccim De Brum, Luana Rossato, Sydney Hartz Alves,Tanise Vendruscolo Dalmolin,Marli Matiko Anraku De Campos,Margareth Linde Athayde (Journal of Applied Pharmaceutical Science, 2013)
With the emergence of antimicrobial resistance, it becomes necessary to search for new alternatives for the treatment of infectious diseases. Solanum guaraniticum is a shrub known as jurubeba or false jurubeba that has hepatoprotective and antioxidant activities, used in popular medicine for the treatment of various diseases. The aim of this study was to evaluate the in vitro antimicrobial and antimycobacterial activities of crude extract, chloroforn, ethyl acetate and butanol fractions from its leaves. Good activities were observed for the ethyl acetate fraction against Staphylococcus intermedius and Listeria monocytogenes (MIC = 64 µg/mL) and for the crude extract against Micrococcus luteus (MIC = 32 µg/mL). In general, the extracts showed moderate activity against Gram-positive bacteria, and were inactive against Gram-negative bacteria and fungi. It was also verified considerable activity against Mycobacterium smegmatis, mainly by chloroform fraction (MIC = 156 µg/mL). These results are probably due to the good antioxidant activity and to the presence of high contents of polyphenols, tannins and alkaloids, metabolites known to possess antimicrobial activity. Studies aiming the isolation of compounds are necessary in order to know the main component involved in these activities, since the plant has an antimicrobial potential.
Keywords: Antimicrobial, antimycobacterial, jurubeba, polyphen